Avaliação da transferência de quantidade de movimento, energia e das espécies químicas em um prato perfurado de destilação através da fluidodinâmica computacional - Justi, Gabriel Henrique (2016)
The development of the design of chemical processes has received increasing improvement, incorporating sophisticated mathematical models, which allowed better simulation of its real behavior. Distillation is one of the most important and used separation techniques of components at industrial level, applied in a wide range of processes and its perfect working and optimization are economically crucial factors. Its great importance is due to the capacity of purify components of a mixture using the volatility difference among them as driving force. However, this technique represents 40% of the total energy consumption of an industrial facility. Some of models used for this, such as the models based on equilibrium and non-equilibrium stage concepts, usually provide useful results, but consider empirically many of the fluid dynamics phenomena by assuming a perfect mixture in each phase. Due to the development of the Information Technology (IT), in the numerical methods and improvement in models of multiphase flows, the investigation of complex turbulent flow problems is possible. One way to investigate these problems is to use the Computational Fluid Dynamics (CFD) tecniques. Therefore, it was adopted for this study a CFD model, with the main objective of evaluating the transport phenomena for the isothermal (water-air) and non-isothermal (ethanol-water) flows through the CFD techniques to simulate a distillation sieve tray. The proposed models had the following characteristics in common in the modeling: heterogeneous, three-dimensional, shear stress transport as turbulence model, and Eulerian-Eulerian approach at 1 atm. The continuity and momentum conservation equations were used to describe the isotherm model and for non-isothermal model it was added the energy and chemical species conservations equations. The simulated sieve trays geometries were based on experimental work of Solari e Bell (1986), to which it were observed the influence of the inlet downcomer presence or not on sieve tray. The results for isotherm flow showed the velocity profiles, the volume fractions, and clear liquid height under the influence of the inlet downcomer. For the non-isotherm flow, the results showed moreover the hydraulic parameters, the temperature profiles and ethanol mass fractions for vapor flow rates. Thus, the simulations of the isothermal system indicated a strong influence of the liquid velocity profile for the domain with downcomer inlet. In the non-isothermal system it was possible to determine the separation efficiency, which varied with the vapor flow rates on the sieve tray. The proposed methodology in this work proved to be appropriate and the computational fluid dynamics techniques presented to be an important tool in the design and optimization of sieve trays.